Anatomical variations of foramen spinosum in South Indian dry skulls - P, Deeksheetha; Saravanan; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Foramen spinosum is an important opening on the infratemporal surface of the greater wing of the sphenoid bone and lies posterolateral to foramen ovale. It transmits the middle meningeal vessels and the nervous spinosus .The aim of the study was to determine the exact size of the foramen spinosum in 50 dry human skulls, on the extra cranial view and in the middle cranial fossa. The study was conducted on 50 dry human skulls of South Indian origin. The skulls used for the research belong to the department of Anatomy in Saveetha Dental College. The foramen were measured using a pair of dividers and a ruler. In our research the length of the foramina that were measured are as follows, , 88% of the foramen lying on the right side are of the sizes between 2.0 and 3.0mm.Whereas, only 12% of the foramen on the right side are of the sizes between 3.1 to 3.5mm. 76% of the foramen lying on the left side are of sizes between 2.0 and 3.0mm. And only 24% of the foramen lying on the left side are of sizes between 3.1 and 3.5mm. Only one foramen on the right side was of size 4.0 mm, while no foramen on the left side was 4.0 mm.